Malondialdehyde Formation in Rat Platelet-Rich Plasma - Livio, M; Rajtar, G; Merino, J; Gaetano, G de (Thrombosis and Haemostasis, 1980)
The type of inhibition and the relative potency of aspirin and indomethacin on rat platelet malondialdehyde (MDA) formation were investigated in an in vitro system. Both drugs inhibited the production of MDA after platelet stimulation with either thrombin (10 or 25 NIH u/ml) or sodium arachidonate (0.5–2.25 mM).Inhibition by both drugs was concentration-dependent, was partially removed when platelet-rich plasma was diluted with platelet-poor plasma, was much stronger when either drug was preincubated with platelets for 10 minutes than for 1 minute and was apparently competitive when analysed by Dixon plots (1/V versus inhibitor concentrations).It is suggested that both aspirin and indomethacin may inhibit in vitro cyclo-oxygenase activity in citrated platelet-rich plasma by a similar, if not identical, partially reversible mechanism, not involving – in a first step – covalent binding of either drug to enzyme.A scheme of the interaction of both drugs with cyclo-oxygenase is presented which also takes into account the irreversible acetylation of the enzyme occurring after longer incubation times with aspirin.
Keywords: Blood platelets; Arachidonic acid metabolism; Malondialdehyde; Thrombin; Aspirin; Indomethacin; Kinetic analysis